Public Services in Municipalities Sustainable Development Policy – Selected Issues - Słupik, Sylwia (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The aim of this study is to identify the main barriers municipalities face and the benefits they gain from implementing sustainable development from authorities point of view. The paper also presents the main directions and activities public authorities have implemented in technical and environmental public services. It also discusses the results of empirical research conducted in 2015 in municipalities in the voivodeships of Wielkopolska, Silesia and Podlasie. The main conclusion of the research is that effectively implementing sustainable development policy largely depends on the awareness and involvement of local authorities. The paper shows that in many municipalities, economic, social and environmental development factors aren’t balanced. Moreover, sustainable development programming and activity should improve the quality of life for inhabitants, but they often fail to leave the planning stage.